Subthreshold Micropulse Laser in Diabetic Macular Edema: 1-Year Improvement in OCT/OCT-Angiography Biomarkers - Vujosevic, Stela (Transl Vis Sci Technol, 2020)
PURPOSE: The aim of this study was to evaluate 1-year quantitative changes in specific inflammatory parameters on optical coherence tomography (OCT) / optical coherence tomography angiography (OCTA) in diabetic macular edema (DME) treated with subthreshold micropulse laser (SMPL). METHODS: Thirty-seven patients / eyes with previously treatment-naïve DME treated with SMPL were prospectively evaluated at 3, 6, and 12 months. Fifteen fellow eyes with only microaneurysms (MAS) not eligible for treatment were controls. Evaluated OCT / OCTA parameters included: central macular thickness (CMT); hyper-reflective retinal spots (HRS); disorganization of inner retinal layers (DRILs); MA in the superficial / deep capillary plexuses (SCP/DCP); cysts in the area at the SCP / DCP; and macular perfusion parameters (MATLAB, version 2017b). RESULTS: In the treated group, mean best corrected visual acuity (BCVA) progressively increased from 69.4 ± 12.0 to 76.0 ± 9.1 Early Treatment Diabetic Retinopathy Study (ETDRS) letters (P < 0.001) at 12 months; HRS decreased from baseline (80.75 ± 20.41) at 3 (73.81 ± 17.1, P = 0.002), 6 (69.16 ± 16.48, P < 0.0001), and 12 months (66.29 ± 18.53, P < 0.0001). MA decreased at 3 months in the DCP (P = 0.015), at 6 and 12 months in both plexuses (P ≤ 0.0007). BCVA, HRS, and MA remained stable in the controls during all follow-ups. DRIL was present in 18 of 37 patients at baseline and progressively decreased from 557.0 ± 238.7 to 387.1 ± 282.1 μm (P = 0.01). The area of cyst decreased both in the SCP (P = 0.03) and the DCP (P = 0.02). CMT and perfusion parameters did not change. CONCLUSIONS: SMPL reduced the number of HRS (sign of activated microglia cells in the retina), MA, DRIL extension, and the area of cysts. Further studies are needed to confirm these preliminary data on the anti-inflammatory effect of SMPL, and to explore the mechanism of action. TRANSLATIONAL RELEVANCE: The follow-up of OCT/OCTA noninvasive biomarkers offers a unique insight in the mechanism of laser action, suggesting an anti-inflammatory effect of SMPL.